2015
DOI: 10.1134/s1029959915030108
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life enhancement by irradiation of 12Cr1MoV steel with a Zr+ ion beam. Mesoscale deformation and fracture

Abstract: The structure and properties of 12Cr1MoV steel irradiated with a zirconium ion beam were studied by optical microscopy, scanning electron microscopy, and micro-and nanoindentation. It is shown that the modification covers the entire cross-section of the irradiated specimens to a depth of 1 mm. The data on irradiation-induced structural changes are used to interpret the changes in mechanical properties of the irradiated specimens under static and cyclic loading. Particular attention is given to analysis of stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the studies of different energy densities, it revealed that the maximal microhardness value is at the condition of Es= (30-40) J/cm 2 but there is no analysis of the effect of energy density on element distribution [16]. The previous investigations highlighted that the different surface treatments (ion beams, currents and energy densities, et al) refine grain size and improve mechanical properties [17][18][19][20]. At present, there is less report about the investigation of the electron beam treating the Al-Mg specimens manufactured by WAAM.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of different energy densities, it revealed that the maximal microhardness value is at the condition of Es= (30-40) J/cm 2 but there is no analysis of the effect of energy density on element distribution [16]. The previous investigations highlighted that the different surface treatments (ion beams, currents and energy densities, et al) refine grain size and improve mechanical properties [17][18][19][20]. At present, there is less report about the investigation of the electron beam treating the Al-Mg specimens manufactured by WAAM.…”
Section: Introductionmentioning
confidence: 99%